1992
DOI: 10.1002/ejsp.2420220104
|View full text |Cite
|
Sign up to set email alerts
|

Context‐dependent variation in social stereotyping 1: The effects of intergroup relations as mediated by social change and frame of reference

Abstract: During the [1990][1991]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
137
2
4

Year Published

1996
1996
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 192 publications
(151 citation statements)
references
References 48 publications
8
137
2
4
Order By: Relevance
“…For example, research from this perspective has shown that (a) identity is fluid and context-dependent (e.g., Onorato & Turner, 2002); (b) social forces (e.g., comparative contexts, intergroup relations) shape how individuals understand the defining features of groups (e.g., Haslam, Turner, Oakes, McGarty, & Hayes, 1992), including those to which they belong (e.g., Simon, 1992), and this has consequences for how they understand their self and act on that basis (e.g., Rabinovich, Morton, Postmes, & Verplanken, 2012), and; (c) people's evaluations of, and emotional reactions to, other people, information, ideas, and events varies as a function of how these things reflect and contribute to their own salient sense of identity (e.g., Dumont, Yzerbyt, Wigboldus, & Gordijn, 2003;Häusser, Kattenstroth, van Dick, & Mojzisch, 2012;Haslam, Jetten, O'Brien, & Jacobs, 2004;Mackie, Worth, & Asuncion, 1990;Morton, Haslam, Postmes, & Ryan, 2006;Schmitt, Silvia, & Branscombe, 2000).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…For example, research from this perspective has shown that (a) identity is fluid and context-dependent (e.g., Onorato & Turner, 2002); (b) social forces (e.g., comparative contexts, intergroup relations) shape how individuals understand the defining features of groups (e.g., Haslam, Turner, Oakes, McGarty, & Hayes, 1992), including those to which they belong (e.g., Simon, 1992), and this has consequences for how they understand their self and act on that basis (e.g., Rabinovich, Morton, Postmes, & Verplanken, 2012), and; (c) people's evaluations of, and emotional reactions to, other people, information, ideas, and events varies as a function of how these things reflect and contribute to their own salient sense of identity (e.g., Dumont, Yzerbyt, Wigboldus, & Gordijn, 2003;Häusser, Kattenstroth, van Dick, & Mojzisch, 2012;Haslam, Jetten, O'Brien, & Jacobs, 2004;Mackie, Worth, & Asuncion, 1990;Morton, Haslam, Postmes, & Ryan, 2006;Schmitt, Silvia, & Branscombe, 2000).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…La competición puede incluir también pugna por estatus o poder. El surgimiento de nuevos estereotipos parece responder a modi¿ caciones en las relaciones económicas o políticas entre los grupos que compiten (Bar-Tal & Labin, 2001;Haslam, Turner, Oakes & McGarty, 1992).…”
Section: Surgimiento De Nuevos Estereotiposunclassified
“…La competición puede incluir también pugna por estatus o poder. El surgimiento de nuevos estereotipos parece responder a modi¿ caciones en las relaciones económicas o políticas entre los grupos que compiten (Bar-Tal & Labin, 2001;Haslam, Turner, Oakes & McGarty, 1992).Indicios de nuevos estereotipos mapuches.Una revisión de la literatura reciente sugiere el surgimiento de dos nuevos estereotipos, ambos desfavorables, sobre los actuales mapuches. Un estereotipo adjudicaría atributos como subversivos, extremistas, prepotentes, que no miden riegos, violentos, peleadores, destructivos, traicioneros, enceguecidos (Amolef, 2004;Merino et al, 2004;.…”
unclassified
“…It also shares with SCT a model of social categories as context-dependent social judgements, based upon a social actor's background ideology and motivations, and that are dynamic in both form and content (Brown & Turner, 2002;Haslam, Turner, Oakes, McGarty, & Hayes, 1992;Reicher, 2001;Turner, Oakes, Haslam, & McGarty, 1994). Moreover, the ESIM proposes that changes in the form and content of a social category lead to changes in the category 'prototype' and therefore, through a process of 'induction', who or what behaviours can become influential among crowd participants (e.g.…”
Section: Social Psychology and Social Changementioning
confidence: 99%